The relationship between disgust sensitivity and BMI: Is the food disgusting or am I?. (September 2021) - Spinelli, Sara; Cunningham, Caitlin; Pierguidi, Lapo; Dinnella, Caterina; Monteleone, Erminio; White, Theresa L.
Highlights: The relationship between disgust sensitivity and BMI differs in obese and non-obese. Restrained eating mediates disgust sensitivity in the prediction of BMI in non-obese. BMI acts as partial mediator of disgust sensitivity in predicting restrained eating. Sensitivity to disgust is associated with lower preference for high-fat dairy products. No relationship was found between PROP status and BMI in either obese or non-obese. Abstract: Core disgust is a negative emotion, comprised of disgust in response to food, animals, and from the body itself (and its products). Individual differences exist in the level to which people experience the emotion of core disgust. Sensitivity to disgust has been associated negatively with Body Mass Index (BMI) in overweight and obese people, and to eating disorders independently from BMI. This study investigates the relationship between disgust sensitivity and BMI by examining data from the Italian Taste Project (n = 2317). We hypothesized that the relationship between disgust sensitivity and BMI, after accounting for age and gender, may be mediated by other factors, such as 6-n-propylthiouracil (PROP) sensitivity or eating restraint, and that this relationship might differ in non-obese and obese individuals. Results showed that the relationship between sensitivity to disgust and food behaviors is complex and differs between obese and non-obese people. Two mediation models were considered. In the first case restrained eating acted as a mediator of disgust sensitivity in the prediction of BMI, while in the second one BMI acted only as a partial mediator of disgust sensitivity in the prediction of restrained eating. This suggests that heightened sensitivity to core disgust may be associated with a heightened sensitivity to self-disgust, motivating restrained eating behaviors when BMI is higher, but only in non-obese individuals.